2011
DOI: 10.1542/peds.2010-1481
|View full text |Cite
|
Sign up to set email alerts
|

High Folate Intake Is Related to Better Academic Achievement in Swedish Adolescents

Abstract: Folate intake had a positive association with academic achievement in the 15-year-olds, which was not attenuated by SES or MTHFR 677 TT homozygosity. These results provide new information that points to the importance of keeping a closer watch on folate status in childhood and adolescence. They may also have direct implications for school meal provisions, school teaching programs, and information to parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
2
20
0
1
Order By: Relevance
“…The sum of school grades for either 17 main subjects or 10 core subjects was used as a measure of academic achievement, and its dependence on tHcy and plasma choline was tested. The previously established strong socioeconomic predictors of school grades (5) were entered as covariates ( i.e. , sex, smoking, and maternal education).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sum of school grades for either 17 main subjects or 10 core subjects was used as a measure of academic achievement, and its dependence on tHcy and plasma choline was tested. The previously established strong socioeconomic predictors of school grades (5) were entered as covariates ( i.e. , sex, smoking, and maternal education).…”
Section: Resultsmentioning
confidence: 99%
“…Against this background, we hypothesized that, in addition to folate, choline and/or betaine might be predictors of academic achievement. We therefore studied academic achievement in 324 children aged 15 yr and measured biomarkers of choline in blood, 2 high‐prevalence single nucleotide polymorphisms affecting their 1‐CM ( MTHFR, PEMT ) (18, 19), and the major socioeconomic factors known to influence school achievement (5).…”
mentioning
confidence: 99%
“…The four studies reviewed here suggest possible specific effects of iron, zinc, folate, vitamin B 12 , and thiamine on physical or cognitive development [27][28][29]31], and it is worth emphasizing the effect these micronutrients also have on hemoglobin status. However, the effects of individual micronutrients are not clear.…”
Section: Performancementioning
confidence: 97%
“…With regard to the role of micronutrients in various cognitive and physical performance outcomes in children, six studies have been published in the past 2 years (Table 3). Academic achievement has been positively linked to folate intake in normal children [28] and a follow-up of children who were fed with a thiamine-deficient milk substitute during infancy up to 7 years of age showed significantly greater language impairment when compared to age-matched children who were fed with other milk sources [29]. For cognition, one fortification study found no effects on cognition in apparently healthy children [18], whereas a supplementation study found that verbal and nonverbal memory improved after supplementation of iron and zinc in deficient children [27].…”
Section: Performancementioning
confidence: 99%
“…Folate intake is also important to prevent cognitive decline in old age and may enhance academic performance in young people [1,2]. The recommended intake for adults is 400 μg/day, with the addition of 200 μg/day during pregnancy and 100 μg/day during breastfeeding [3].…”
Section: Introductionmentioning
confidence: 99%